Studies on the cocoyam rot in Nigeria - MADUNAGU, BENE E. (Indian Phytopathology, 2012)
Corns of cocoyam (Colocasia antiquorum] Schott were vulnerable to both soft and dry rots. The pathogens associated with the soft rot were Botryodiplodia theobromae Pat., Fusarium moniliforme var subgluiinans Wr and Ng., Aspergillus niger Van Tiegham; a bacterium Serratia sp and a nematode, Scuiellonema sp. The pathogens associated with the dry rot were Aspergillus flavus Link; Fusarium solani (Mart) Appel and Wollenw and Fusarium coeruleum (Lib.) Sacc. The pathogens were found to penetrate the host corms through wounds and bruises. Some environmental factors were found to enhance the establishment and extent of disease development. Disease development was the highest when temperature of storage was 30Â°C and RH 100 per cent. Borax, biphenyl and bordeaux mixture were effective in controlling the rotting. Placing corms well spread out on clean planks, placed on the cool floor, can minimise the rotting process. Dusting corms with soot before storage also checked incidence of rotting.